Case Report: Medial prefrontal syndrome in a coup de sabre scleroderma carrier (2023)
Introduction: Linear scleroderma en coup de sabre is a subtype of scleroderma hallmarked by cutaneous and extracutaneous manifestations in which neurological symptoms can be a predominant feature of this condition. Case presentation: We report a case of a previously healthy 47-year old male who developed neuropsychiatric symptoms and right-sided cephalalgia for two months. Clinical examination revealed a right frontoparietal cutaneous lesion and neurological findings suggesting a medial prefrontal syndrome. The neuroimaging evaluation identified scalp and bone thinning adjacent to the skin lesion and cortical subcortical white matter hyperintensity due to vasogenic oedema at the right frontal and parietal region. A biopsy from the affected area revealed reactive gliosis. Conclusion: To our knowledge, this is the first linear scleroderma en coup de sabre report associated with a neurological involvement typical of a medial prefrontal syndrome. This case highlights the importance of clinical acuity in recognising atypical phenotypes within the spectrum of this uncommon disease.